Perverse Incentives in the Medicare Prescription Drug Benefit - David McAdams; Michael Schwarz (SAGE Publishing, 2007)
This paper analyzes some of the perverse incentives that may arise under the current Medicare prescription drug benefit design. In particular, risk adjustment for a standalone prescription drug benefit creates perverse incentives for prescription drug plans when making coverage decisions and/or for pharmaceutical companies when setting prices. This problem is new in that it does not arise with risk adjustment for other types of health care coverage. For this and other reasons, Medicare's drug benefit requires especially close regulatory oversight, now and in the future. We also consider a relatively minor change in financing the benefit that could lead to significant changes in how the benefit functions. In particular, if all plans were required to charge the same premium, there would be less diversity in quality, but also less need to regulate formulary composition, less budgetary uncertainty, and less upward pressure on drug prices.